Estudio de factibilidad para la creación de una empresa prestadora de servicios de transporte escolar hacia centros de formación en la ciudad de Quevedo año - 2013 - Anchaguano Jácome, Jessica Katherine (2013)
The present study found framed within the modality of feasible project, oriented to the installation and commissioning of a transport company, located in the city of Quevedo, Los Ríos province. Among the objectives are the following: the study of market through field research to educational centers, for the creation of the company with an excellent customer service, develop a technical study of financial and investment on the project. Assess actual and potential resources required for the new company. Determine the point of equilibrium for the new company. The design of the research, was descriptive, since it was developed with primary sources processed through the application of a survey questionnaire, the inhabitants of the canton. Among the results of the investigation it was determined that there is an unmet demand. The investment required for the project turned out to be $152392.51, which 70% will be covered by financing from a financial institution and the remaining 30% for own contribution. Finalizing calculations and financial analysis determined the feasibility of the project, since revenues are obtained in the first year by $85,200.00; VAN $199,409.61; TIR 17.25% and relationship benefit cost of 2.08.